Introducing and Development of Cassava Rengginang MSMEs “Bu Tarni” Pagerukir Village: NIB and Halal Certification - Setiyawan, Doni; Nurhidayat, Saiful; Saputri, Frensiska; Setyawidyastuti, Mey; Cahyani, Adelia (CV. BImbingan Belajar Assyfa, 2024)
The surge in micro, small, and medium-sized enterprises (MSMEs) highlights their vital role in Indonesia's economy by generating employment and fostering innovation. Despite the introduction of the NIB (Business Identification Number) system to streamline business registration, many micro and small entrepreneurs lack the knowledge to obtain necessary business licenses and halal certification. This study focuses on educating and assisting Rengginang cassava entrepreneurs, specifically